Interferon induced Mx protein from Indian snow trout Schizothorax richardsonii (Gray) lacks critical functional features unlike its mammalian homologues. (April 2018) - Saxena, Ankur; Belwal, Kiran; Chauhan, Ankita; Pande, Amit
Graphical abstract: Highlights: Snow trout Mx protein carries the signature of dynamin family (LPRGTGIVTR) and a tripartite GTP-binding domain (GDQSSGKS, DLPG, and TKPD). Mx protein is an elongated structure with a G domain, bundle signaling element (BSE) and a GTPase effector domain with two highly conserved leucine zippers at C treminal. Snow trout Mx lacks the crucial functional features of its mammalian homologues. A potential ligand binding site was identified in G-domain of Mx. Abstract: Viral attack within host cells triggers the production of type I interferons and leads to the induction of interferon stimulated genes (ISGs). One of the ISG Mx, encodes type I interferon inducible GTPase that is responsible for the establishment of an anti-viral state within cells. Intriguingly, several isoforms of Mx have been reported in fish, but the structural analysis of fish Mx proteins remains unexplored. For the first time, we have identified and unraveled the molecular structure of Mx protein from Indian snow trout, Schizothorax richardsonii (Gray) a Coldwater fish that inhabits the water bodies in the sub-Himalayan region. The snow trout Mx coding region consists of 2518 nucleotides with an open reading frame (ORF) of 1854 nucleotides. It codes for a polypeptide of 617 amino acids with a predicted molecular weight of 70 kDa. In silico analysis of snow trout Mx protein revealed signature of dynamin family (LPRGTGIVTR) along with a tripartite GTP-binding domain (GDQSSGKS, DLPG, and TKPD). Homology modelling established that the Mx protein is an elongated structure with a G domain, bundle signaling element (BSE) and a GTPase effector domain (GED). Moreover, the GED of Mx contains two highly conserved leucine zippers at the COOH-terminal of the protein suggesting its structural similarity with human homologues. However, snow trout Mx lacks the essential features of its mammalian homologues questioning its functional characteristics. Further, a ligand binding site in the said protein has also been predicted adjacent to the GTPase switch within the G domain.